Quilombolas e jongueiros: uma etnografia nas comunidades de Linharinho e Porto Grande, Conceição da Barra (ES) - Rodrigues, Luiz Henrique (2016)
This work develops a reflection on the ways in which jongueiras quilombolas communities, specifically Linharinho and Porto Grande, located in the territory of Sapê of North, in the northern region of the state of the Espírito Santo, are taking jongo practices, recognized as cultural heritage of Brazil, as cultural references to demarcate their identities. It is also a product of observation and analysis of how some jongueiras and caxambuzeiras communities of southeastern Brazil are claiming from the safeguard policies of the assets recorded as Brazilian cultural heritage, recognition of their identities and their territories, as well as guarantee their ethnic rights. Finally, the dissertation analyzes, from the ethnography in the quilombolas communities of Porto Grande and Linharinho, forms of social and political organization, as well as their creations and recreations of cultural and religious patrimonies.